Growth and Jobs in Slavonia, Baranja, and Srijem : Rapid Diagnostics - World Bank (World Bank, Washington, DC, 2020)
Slavonia’s economy is now amongst the poorest in the European Union (EU) and has been growing more slowly than comparable regions. Some Polish and Romanian counties were less advanced until 2013 but have now overtaken Slavonia. Achieving a turnaround is difficult: only 9 percent of lagging regions in the EU have managed to graduate. Part of the answer lies in smart use of EU funds, as demonstrated by Pomorskie region in Poland. Top priority actions to seize these opportunities can be taken by ministers, county prefects, and regional coordinators. Each opportunity is constrained by several issues: a lack of collaboration within Slavonia; a need for national reforms; and alignment of ministries around shared priorities. The decisions to unlock these constraints are outlined in the report.